The Influence of Family and Friends on Geographic Labor Mobility: An International Comparison - Levy, Mildred B.; Wadycki, Walter J. (The Review of Economics and Statistics, 1973)
Mildred B. Levy, Walter J. Wadycki, The Influence of Family and Friends on Geographic Labor Mobility: An International Comparison, The Review of Economics and Statistics, Vol. 55, No. 2 (May, 1973), pp. 198-203